Step up transformer - Nikolayevich Sukhanov , Vladimir (International Journal of Engineering and Technology, 2024)
The operation of new electrical step–up transformer is based on the principle of induction of electromotive force in an electrical conductor surrounded by a magnetic circuit. The new design of the transformer with a semiconductor secondary winding is presented. Such a transformer, for all its traditional simplicity, has an arbitrarily large transformation ratio.